Microcytosis in Erythropoietic Protoporphyria - Graziadei, Giovanna; Duca, Lorena; Granata, Francesca; De Luca, Giacomo; De Giovanni, Anna; Brancaleoni, Valentina; Nava, Isabella; Di Pierro, Elena (Frontiers in Physiology, 2022)
Partial deficiency of the last enzyme of the heme biosynthetic pathway, namely ferrochelatase (FECH), is responsible for erythropoietic protoporphyria (EPP) in humans. This disorder is characterized by painful skin photosensitivity, due to excessive protoporphyrin IX (PPIX) production in erythrocytes. Although several papers report the presence of iron deficiency anemia in about 50% of EPP patients, there is still no a conclusive explanation of the why this occurs. In the present work, we explored haematological indices and iron status in 20 unrelated Italian EPP patients in order to propose a new hypothesis. Our data show that microcytosis is present in EPP patients also in the absence of anemia and iron deficiency with a link between PPIX accumulation and reduced MCV, probably indicating an indirect condition of heme deficiency. Patients studied had a downward shift of iron parameters due to increased hepcidin concentrations only in a state of repleted iron stores. Interestingly, haemoglobin synthesis was not limited by iron supply except in cases with further iron loss, in which concomitantly increased soluble transferrin (Tf) receptor (sTfR) levels were detected. The mechanisms involved in the iron uptake down-regulation in EPP remain unclear, and the role of PPIX accumulation in microcytosis.